Eksistensi Pengadilan Perikanan dalam Mengadili Perkara Tindak Pidana Perikanan di Indonesia - Irwandi Syahputra; Endri; Eki Darmawan; Heni Widiyani; Tike Murti Sari Dewi; Sebastian Alboen Sihombing (Fakultas Hukum Universitas Riau, 2024)
As long as a fisheries court other than the fisheries court has not been established, criminal cases in the fisheries sector that occur outside the jurisdiction of the fisheries court will still be examined, tried and decided by the competent district court. Such provisions create a dualism in the legal regime, namely the legal regime of the district court and the regime fisheries court law. With the examination of criminal acts in the fisheries sector carried out by the fisheries courts and district courts, there is dualism and legal uncertainty in the handling of fisheries crimes. Several formal laws are specifically regulated in the Fisheries Law, namely the existence of Ad Hoc Judges, Trials without the Presence of the Defendant (In Absentia), Periods of Court Decisions, Determinations and Detention Periods by Judges and Registrars. Fisheries Courts that have been established have made a major contribution in law enforcement, all established fisheries courts have issued several decisions on fisheries cases. The implementation of administrative sanctions in the implementation of the Job Creation Law also affects the existence of fisheries courts in adjudicating fisheries criminal cases. For fisheries crimes committed in the ZEEI region by foreign vessels, the criminal sanctions contained in the Fisheries Law are still applie